Participatory action research approaches and methods : connecting people, participation and place - Kindon, Sara Louise; Pain, Rachel; Kesby, Mike, 1966- (London ; New York : Routledge, 2007)
This book examines the justification, theorisation, practice and implications of participatory action research approaches and methods in the social and environmental sciences.
Includes bibliographical references (p. [231]-249) and index.
Keywords: Social participation -- Research -- Methodology; Political participation -- Research -- Methodology; Communities -- Research -- Methodology